Overexpression of miR-451a in sepsis and septic shock patients is involved in the regulation of sepsis-associated cardiac dysfunction and inflammation - Wang,Heng (2020)
Abstract The purpose of this study was to investigate the expression and clinical value of microRNA-451a (miR-451a) in septic patients and analyze its effect on sepsis-associated cardiac dysfunction and inflammation response. A rat model of sepsis was constructed by cecal ligation and puncture. The expression of miR-451a was measured by quantitative real-time PCR. Receiver operating characteristic (ROC) analysis was used to assess the diagnostic value of serum miR-451a. The cardiac function and inflammatory responses in septic rats were measured to explore the functional role of miR-451a. Serum expression of miR-451a was increased in septic patients compared with healthy controls, and had the ability to distinguish septic patients from healthy volunteers with a sensitivity and specificity of 87.8% and 81.5%, respectively. Elevated serum miR-451a was associated with sepsis severity, as evidenced by the increased expression of miR-451a in septic shock patients and its correlation with key clinical indicators. Significantly upregulated expression of miR-451a was found in septic patients with cardiac dysfunction, and the knockdown of miR-451a in sepsis rats improved cardiac function and inhibited inflammatory responses. All the data revealed that serum miR-451a serves as a candidate diagnostic biomarker of sepsis and a potential parameter to indicate disease severity. The reduction of miR-451a may mitigate sepsis-induced cardiac dysfunction and inflammatory responses.